2018
DOI: 10.1115/1.4039789
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Performance Characterization Method for Comparing PEFCs of Varying Channel Dimensions

Abstract: A method which allows for the comparison of polymer electrolyte fuel cell (PEFC) bipolar plates (BPs) with various channel dimensions is outlined here. It is applied to data from an experiment with different channel and land width and channel depth combinations for interdigitated and parallel designs. Channel and land width and channel depth varied from 0.25 mm to 1 mm on six different BP designs, and two stoichiometries were tested. Each condition was performed three times for repeatability. The method calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Channel geometry, including land width, channel width, and channel depth, significantly influences two-phase flow behavior and impacts PEMFC performance. Extensive in-situ experimental testing over a wide range of channel dimension combinations with depths and widths ranging from 0.25 mm to 1 mm has shown that optimal performance, accounting for pumping power at higher pressures, is achieved at a hydraulic diameter of ~0.4 mm for certain ranges of stoichiometry (59,60). Other results focusing on channel and rib widths (in parallel designs) have…”
Section: Channels and Flow Fieldsmentioning
confidence: 99%
“…Channel geometry, including land width, channel width, and channel depth, significantly influences two-phase flow behavior and impacts PEMFC performance. Extensive in-situ experimental testing over a wide range of channel dimension combinations with depths and widths ranging from 0.25 mm to 1 mm has shown that optimal performance, accounting for pumping power at higher pressures, is achieved at a hydraulic diameter of ~0.4 mm for certain ranges of stoichiometry (59,60). Other results focusing on channel and rib widths (in parallel designs) have…”
Section: Channels and Flow Fieldsmentioning
confidence: 99%